Financial planning on health protection for retirees: a cross-border comparative study - Che Mohd Salleh, Marhanum; Chowdhury, Matin; Megat Laksana, Nan Noorhidayu; Razali, Siti Salwani; Abdullah, Nurdianawati Irwani (2019)
Most retirees in Malaysia are the population which their needs are often taken for granted and overlooked. It’s very unfortunate that these categories of people are actually the one that needs a lot in order to sustain their lives. Among them may include universal health coverage, financial risk protection, access to quality essential health-care services and access to safe, effective, quality and affordable essential medicines and vaccines for all. This concept paper is designed to study the importance of a sound healthcare protection for retirees in Malaysia. Several efforts which have been done by the government in Malaysia and some other countries to meet the needs of having the healthcare protection are critically examined with aim to develop a Takaful policy to cover the health services over the retirement period for all retirees in Malaysia.